Drug delivery systems and cartilage tissue engineering scaffolding using marine-derived products - Silva, Tiago H. (2015)
Nature is constantly surprising us with examples of outstanding features, being them of chemical, morphological or biological nature, inspiring scientists towards innovative routes. In particular, marine environment has been receiving growing attention and the advent of marine (blue) biotechnology is strongly contributing to it, in much extent approaching its health (red) counterpart, fostering new therapeutic proposals. Several marine biomaterials are currently being proposed for the sustained delivery of bioactive compounds, often triggered by external stimuli, which may be combined with polymeric matrices for cell culture, on the development of the so-called functional biopolymers. Chitosan and alginate are the most common examples, but other marine origin materials start to find their place, namely the sulfated polysaccharides from seaweeds (p.e. carrageenans) and collagens extracted from marine organisms. Nevertheless, the challenges faced are still high: one benefits from the knowledge acquired with other biopolymers and from keen scientists, but thrilling examples of marine functional biomaterials for cartilage regeneration are still scarce, particularly when considering their in-vivo performance. Those are needed to act as landmarks and inspiration for further developments, namely to instigate the investment of the private biomedical industry to take them into clinics. Current pathologies of articular cartilage are daring us to find ultimate therapeutic solutions and we expect to contribute to the needed discussion with the present chapter, pointing examples of marine functional biomaterials and proposing possible paths to be followed.